Semisynthesis and optimization of G protein‐coupled receptor mimics. (4th August 2014) - Abel, Sabine; Geltinger, Bernhard; Heinrich, Nadja; Michl, Dagmar; Klose, Annerose; Beyermann, Michael; Schwarzer, Dirk
<x xml:space="preserve">Abstract</x> We have recently developed a soluble mimic of the corticotropin‐releasing factor receptor type 1 (CRF1), a membrane‐spanning G protein‐coupled receptor, which allowed investigations on receptor–ligand interactions. The CRF1 mimic consists of the receptor N‐terminus and three synthetic extracellular loops (ECL1–3), which constitute the extracellular receptor domains (ECDs) of CRF1, coupled to a linear peptide template. Here, we report the synthesis of a modified CRF1 mimic, which is more similar to the native receptor possessing a cyclic template that displays the ECDs in a more physiological conformation compared with the initial linear design. In order to facilitate detailed biophysical investigations on CRF1 mimics, we have further established a cost‐efficient access to the CRF1 mimic, which is suitable for isotopic labeling for NMR spectroscopy. To this end, the loop‐mimicking cyclic peptide of the ECL2 of CRF1 was produced recombinantly and cyclized by expressed protein ligation. Cyclic ECL2 was obtained in milligram scale, and CRF1 mimics synthesized from this material displayed the same binding properties as synthetic CRF1 constructs. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.